The Effect of Oral Corrective Feedback (CF) on EFL Learners' Motivation in Communicative Classrooms - Alsolami, Turki (Technium Social Sciences Journal, 2021)
It is currently unclear how the oral corrective feedback (CF) in the speaking process affects the motivation of English as a Foreign Language (EFL) learners to speak in communicative classrooms. The current study intended to address this problem by testing whether EFL learners’ motivation by correcting their errors is influenced significantly by corrective feedback while not causing any demotivation to the learners to speak in a second language (L2) one way or another. As per the results of the analysis of the gathered primary data in the study, it was found that the participants were not only greatly motivated to correct their errors by the corrective feedback, but on the other hand, they were demotivated from speaking. The study therefore concluded that corrective feedback makes EFL learners in Saudi Arabian secondary school classrooms motivated enough to correct their errors, but simultaneously demotivates them from speaking.